Docker for Java developers - Lelek, Tomasz; Safari eBooks ([Place of publication not identified] : Packt, 2018)
"Docker is the world's leading software container platform. Developers use Docker to eliminate "works on my machine" problems when collaborating on code with co-workers. Docker is a command-line program, a background daemon, and a set of remote services that take a logistical approach to solve common software problems. This course starts with the key concepts of containerization and Docker. Next, you'll see the need for containerization and how Docker is tackling those problems. You will build and monitor the status of containers using the Docker shell, and supervise containers. Then, using a Docker file, you'll create a simple java application that will be containerized inside Docker. All installation will be easily distributed in a Docker image that contains Java. The final section is dedicated to more advanced use cases, and you'll see how to automate more complex architectures using Docker."--Resource description page.
Title fromtitle screen (viewed April 17, 2018).
Release date from resource description page (Safari, viewed April 17, 2018).
Presenter, Tomasz Lelek.
Keywords: Application software -- Development -- Automation; Java (Computer program language); Computing platforms; Electronic books